Perjalanan Mas : memoir Muhammad Ariff Ahmad - Mas, 1924-; Raman Daud; Sulhan Rawi (Singapore : Angkatan Sasterawan'50, 2003)
Autobiography of Muhammad Ariff Ahmad, a Singaporean author and prominent personality active in Malay language, literary works, and culture in Singapore.
In Malay.
Keywords: Mas, -- 1924-; Authors, Singaporean -- Biography; Singaporean literature (Malay).